Bi Catalyzed CdS Nanowires With Temperature-Dependent Morphologies for Potential Applications in Solar Cells - Zayas-Bazán, P. G.; Gutierrez Z-B, K.; de Melo, O.; Santana, G.; Sastré-Hernández, J.; Aguilar-Hernández, J. R.; Tufiño-Velázquez, M.; Contreras-Puente, G. (Frontiers in Materials, 2020)
In this work, we present the preparation of CdS nanowires (CdS NWs) using the chemical vapor deposition technique and bismuth (Bi) nanoparticles as catalysts. The obtained nanowires were found to be in the hexagonal Greenockite structure according to XRD diffractograms and Raman spectroscopy measurements. Depending on the growth temperature, two kinds of morphologies were observed in SEM images. At low temperature (around 150°C), a high density and homogeneous population of thin and straight nanowires grown through the vapor–liquid–solid mechanism was observed. At higher temperature (around 270°C), thicker bunches of braided nanowires were observed. A quantitative analysis of the temperature-dependent photoluminescence spectra of the CdS NWs was carried out.